Potential Biomarkers to Predict Acute Ischemic Stroke in Type 2 Diabetes - Moin, Abu Saleh Md; Nandakumar, Manjula; Al-Qaissi, Ahmed; Sathyapalan, Thozhukat; Atkin, Stephen L.; Butler, Alexandra E. (Frontiers in Molecular Biosciences, 2021)
Background and Purpose: Patients with type 2 diabetes (T2D) have increased risk of cardiovascular disease (CVD), encompassing myocardial infarction, stroke and peripheral vascular disease. We hypothesized that those biomarkers indicative of acute ischemic stroke (AIS) seen in large vessel occlusion (LVO) may be also be elevated in T2D and further enhanced by stress conditions; therefore, these proteins represent potentially predictive biomarkers for those T2D patients at high risk of AIS. Methods: We performed an exploratory proteomic analysis in control subjects (n=23) versus those with type 2 diabetes (T2D) (n=23) who underwent a hyperinsulinemic clamp study to transient severe hypoglycemia (blood glucose <2.0mmol/L (36mg/dL)) in a prospective case-control study. We compared these proteins described as diagnostic and prognostic biomarkers for AIS due to LVO: lymphatic vessel endothelial hyaluronic acid receptor-1 (LYVE1), thrombospondin-1 (THBS1), pro-platelet basic protein (PPBP) and cadherin 1 (CDH1). Results: At baseline (BL), PPBP (p<0.05), THBS1 (p<0.05) and CDH1 (p<0.01) were elevated in T2D; LYVE1 was not different between controls and T2D subjects at BL or at subsequent timepoints. PPBP and THBS1 tended to increase at hypoglycemia in both cohorts, though significant only in controls (p<0.05), returning to BL levels post-hypoglycemia. CDH1 levels were higher in T2D at BL, at hypoglycemia and up to 2-hours posthypoglycemia, thereafter reverting to BL levels. Conclusions: Elevated levels of PPBP, THBS1 and CDH1, circulatory proteins suggested as biomarkers of AIS due to LVO, in T2D patients may be prognostically indicative of a cohort of T2D patients at increased risk of ischaemic stroke. Prospective studies are needed to determine if this reflects future clinical risk.